Student Loans and Homeownership - Mezza, Alvaro; Ringo, Daniel; Sherlund, Shane; Sommer, Kamila (Journal of Labor Economics, 2020)
We estimate the effect of student loan debt on subsequent homeownership in a uniquely constructed administrative dataset for a nationally representative cohort. We instrument for the amount of individual student debt using changes to the in-state tuition rate at public 4-year colleges in the student's home state. A $1, 000 increase in student loan debt lowers the homeownership rate by about 1.5 percentage points for public 4-year college-goers during their mid 20s, equivalent to an average delay of 2.5 months in attaining homeownership. Validity tests suggest that the results are not confounded by local economic conditions or changes in educational outcomes.